The ‘Faust’ or ’Lucifer’ Sonata? On Liszt’s idea of programme music as exemplified by his Piano Sonata in B minor - Polony, Leszek (Interdisciplinary Studies in Musicology, 2018)
The musicological tradition places Liszt’s Sonata in B minor within the sphere of compositions inspired by the Faustian myth. Its musical material, its structure and its narrative exhibit certain similarities to the ‘Faust’ Symphony. Yet there has appeared a different and, one may say, a rival interpretation of Sonata in B minor. What is more, it is well-documented from both a musical and a historical point of view. It has been presented by Hungarian pianist and musicologist Tibor Szasz. He proposes the thesis that the Sonata in B minor has been in fact inspired by Milton’s Paradise Lost, with its three protagonists: Adam, Satan and Christ. He finds their illustrations and even some key elements of the plot in the Sonata’s narrative. But yet Milton’s Paradise Lost and Goethe’s Faust are both stories of the Fall and Salvation, of the cosmic struggle between good and evil. The triads of their protagonists - Adam and Eve, Satan, and Christ; Faust, Mephisto and Gretchen - are homological. Thus both interpretations of the Sonata, the Goethean and the Miltonian, or, in other words, the Faustian and the Luciferian, are parallel and complementary rather than rival. It is also highly probable that both have had their impact on the genesis of the Sonata in B minor.